The ozone response to ENSO in Aura satellite measurements and a chemistry‐climate simulation. Issue 2 (24th January 2013) - Oman, Luke D.; Douglass, Anne R.; Ziemke, Jerry R.; Rodriguez, Jose M.; Waugh, Darryn W.; Nielsen, J. Eric
Abstract : [1] The El Niño–Southern Oscillation (ENSO) is the dominant mode of inter‐annual variability in the tropical ocean and troposphere. Its impact on tropospheric circulation causes significant changes to the distribution of ozone. Here we derive the lower tropospheric to lower stratospheric ozone response to ENSO from observations by the Tropospheric Emission Spectrometer (TES) and the Microwave Limb Sounder (MLS) instruments, both on the Aura satellite, and compare to the simulated response from the Goddard Earth Observing System Chemistry‐Climate Model (GEOSCCM). Measurement ozone sensitivity is derived using multiple linear regression to include variations from ENSO as well as from the first two empirical orthogonal functions of the quasi‐biennial oscillation. Both measurements and simulation show features such as the negative ozone sensitivity to ENSO over the tropospheric tropical Pacific and positive ozone sensitivity over Indonesia and the Indian Ocean region. Ozone sensitivity to ENSO is generally positive over the midlatitude lower stratosphere, with greater sensitivity in the Northern Hemisphere. GEOSCCM reproduces both the overall pattern and magnitude of the ozone response to ENSO obtained from observations. We demonstrate the combined use of ozone measurements from MLS and TES to quantify the lower atmospheric ozone response to ENSO and suggest its possible usefulness in evaluating chemistry‐climate models. Key Points: We derive the ozone response to ENSO from Aura satellite Good continuity in MLS/TES derived sensitivity GEOSCCM can largely reproduce this response